(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The autor examines in the article the different dialectisms’ levels in the poetic works of Ivan Malkovych. Particular attention is drawn to the lexical dialectisms: it was determined their classification according to the parts of language, the semantic groups and the role in the poetic texts.